MODEL MATEMATIKA PENYEBARAN VIRUS NIPAH (NiV) DENGAN KONTROL OPTIMAL MENGGUNAKAN METODE PONTRYAGIN MAXIMUM PRINCIPLE (PMP) - Nur Ilmayasinta; Annisa Rahmita Soemarsono; Erra Noer Rohmania Aishwaray (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2022)
The use of optimal intervention strategies to prevent the spread of Nipah virus (NiV) by applying optimal control approaches is discussed in this article. To begin, we developed a dynamic model of NiV infection as well as three control strategies: public awareness, treatment, and quarantine. The study's goal was to lower the number of affected patients while lowering the three control costs. The Pontryagin maximum concept will be used to characterize optimal control, followed by numerical simulations using the Runge Kutta method of order 4. The simulation findings suggest that the optimal control technique is effective in reducing the appropriate cost of infected individuals while also providing three ideal controls. Early control measures can also effectively prevent the spread of the Nipah virus, according to numerical simulations